Improving fragment-based ab initio protein structure assembly using low-accuracy contact-map predictions - S. M. Mortuza (Nature Portfolio, 2021)
Predicting protein structure from sequence is still not possible for all proteins. Here, the authors introduce a method that integrates deep learning and information about protein co-evolution to guide the prediction of non-homologous protein structures with greater accuracy.